Extracorporeal shockwave therapy (ESWT) in Achilles tendinopathy. A long-term follow-up observational study - Vulpiani, M. C.; Trischitta, D.; Trovato, P.; Vetrano, M.; Ferretti, A. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The etiology, pathogenesis and natural course of Achilles tendinopathy are not yet completely known. Various forms of therapies, either conservative or surgical, have been proposed for its treatment. In the last few years, extracorporeal shockwave therapy (ESWT) has been proposed in the treatment of these tendinopathies and has shown encouraging short-term results. The purpose of this type-C study was to evaluate the effectiveness of ESWT in the symptomatic treatment of Achilles tendinopathies over time. Methods. One hundred five patients (127 tendons) aged between 18 and 74 years (mean age 47.8) were enrolled in this study. All patients underwent clinical and instrumental diagnosis (ultrasonography, magnetic resonance imaging and X-rays) in order to identify presence, location and seriousness of the specific tendinopathy. The symptomatology was classified using the Visual Analogical Scale (VAS) and according to a five-stage clinical evaluation range. Shock wave treatment was applied with an electromagnetic shock wave generator. The protocol consisted in an average of four sessions (minimum three, maximum five), at a 2/7-day interval. In each session 1 500-2 500 impulses were administered with an energy varying between 0.08 and 0.40 mJ/mm2. All patients were evaluated before therapy and two months after the last ESWT session. Also, all patients were assessed and evaluated at medium-term (6 to 12 months), and 121 patients also at long-term (13 to 24 months). Results. Authors obtained satisfactory results in 47.2% of cases (60 out of 127 tendons) at two-months follow-up, which increased to 73.2% at medium-term follow-up (93 out of 127 tendons), and then reaching 76% in the last evaluation (92 out of 121 tendons). Conclusion. The outcome of the described shock wave treatment appears to be satisfactory and confirms the role of this alternative treatment in the management of the tendon disorders.